Legacy and Athlete Preferences at Harvard - Arcidiacono, Peter; Kinsler, Josh; Ransom, Tyler (Journal of Labor Economics, 2022)
We use public documents from the Students for Fair Admissions v. Harvard University lawsuit to examine admissions preferences for recruited athletes, legacies, those on the dean’s interest list, and children of faculty and staff (ALDCs). More than 43% of white admits are ALDC; the share for African American, Asian American, and Hispanics is less than 16%. Our model of admissions shows that roughly three-quarters of white ALDC admits would have been rejected absent their ALDC status. Removing preferences for athletes and legacies would significantly alter the racial distribution of admitted students away from whites.